Qualifications and Competencies of SLSU Guidance Counselors - Daya, Helene D. (JPAIR Multidisciplinary Research, 2009)
The study was intended to assess the qualifications and competencies of Southern Luzon State University counselors of Lucban, Quezon. The study use descriptive survey and correlation research design. As for the statistical measures and tools, tabulation, frequency and percentage distribution were used in presenting the profile of the counselors. The weighted mean was used in identifying which area of competencies has a great extent or limited extent. Likewise, the F-test was used to determine the significant difference between and among the respondents as to the extent of competencies as perceived by the administrators, the faculty and the guidance counselors themselves. The findings reveal that majority of the guidance counselors, as perceived by the administrators have a moderate extent of competency, the same as perceived by the faculty. Moreover, there is a significant difference between and among the respondents as to the extent of competencies of guidance counselors. It can be concluded that most of the guidance counselors are not qualified and competent to be counselors. Guidance counselors rated themselves the highest among the three evaluators as to the competencies of a counselor.